The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1558944716660555he
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Fixation for Scaphoid Nonunion With Bone Grafting Through the Distal Insertion Hole of a Fully Threaded Headless Screw

Abstract: Introduction: Avascular necrosis of the lunate in Systemic Lupus Erythematous (SLE) and rheumatoid arthritis (RA) are not rare. Our study aimed to describe the histopathology of the lunates after removing them in the operating room in patients with rheumatoid diseases and lunate palmar dislocation. We correlated the histopathological findings with magnetic resonance imaging (MRI), radiological parameters, and blood test parameters. Methods: From January 2006 to January 2015, 12 patients were operated for rheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…12 Existem dois estudos na literatura com técnica semelhante à nossa. Ohta et al 13 relatam excelentes resultados de seis não consolidações escafoides tratadas por fixação percutânea com curetagem e enxerto ósseo através do orifício de inserção distal de um parafuso totalmente roscado sem cabeça. Similarmente, Bokhari et al 14 usaram agulha de trocarte Jamshidi para enxerto percutâneo para 15 não consolidações fibrosas escafoides.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…12 Existem dois estudos na literatura com técnica semelhante à nossa. Ohta et al 13 relatam excelentes resultados de seis não consolidações escafoides tratadas por fixação percutânea com curetagem e enxerto ósseo através do orifício de inserção distal de um parafuso totalmente roscado sem cabeça. Similarmente, Bokhari et al 14 usaram agulha de trocarte Jamshidi para enxerto percutâneo para 15 não consolidações fibrosas escafoides.…”
Section: Discussionunclassified
“…A diferença entre esses dois estudos e o nosso é que eles foram realizados em pacientes com não consolidação fibrosa (Slade e Dodds tipo 2) em vez de não consolidação cística. 13,14 Em outro estudo, 33 pacientes sem deformidade corcunda, NAV no polo proximal ou artrite, foi aplicado enxerto percutâneo com pino corticoespojoso, enxerto esponjoso colhido da ala ilíaca e sem fixação adicional, e a consolidação foi obtida a uma taxa de 76%. 15 No presente estudo, a consolidação foi obtida em 9 dos 11 pacientes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Vanhees et al 15 have reported achieving 94% union in a case series of 16 patients treated using a percutaneous technique where the mean time to union was 4 months (17 weeks). Recently, favorable results and high union rates with percutaneous techniques have been reported in multiple studies, [12][13][14] although the exact time to union has not been reported in all the studies. The major risk factors involved in the failure of treatment for this condition are the duration between the injury and the surgical treatment, as well as the localization of the nonunion in the proximal pole 25 (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The union rate and healing potential with percutaneous [11][12][13][14][15] and arthroscopically assisted [16][17][18][19][20] techniques for the treatment of scaphoid nonunion have not been discussed at length. Indeed, comparative studies of different treatment options are rare in the literature.…”
mentioning
confidence: 99%